The use of non-traditional plant raw materials for the recipe composition of chips - O. V. Perfilova; K. V. Bryksina; Z. Y. Rodina (Новые технологии, 2023)
The production of multicomponent chips is currently relevant, since the combination in the formulation of various plant ingredients rich in physiologically active substances can ensure that the finished product contains a complex of functional components. The article investigates the possibility of using plant materials such as apple pomace puree, pumpkin puree, corn flour and calendula powder when creating a recipe composition for new types of chips for healthy diet. The choice of apple pomace is due to the need for their processing due to the transfer of some of the beneficial nutrients of the original apples into them. According to the results of a tasting assessment on a 10-point scale, taking into account the weight coefficients of organoleptic indicators, the maximum number of points of 9.5 and 10 was scored by samples of chips, where the ratio of apple pomace puree and pumpkin puree was 70:30, and the proportion of corn flour and calendula powder to fruit vegetable mass was 5, 10 and 1%, respectively. The influence of different ratios of plant ingredients in the chips formulation on their organoleptic, calorimetric characteristics, as well as antioxidant value was analyzed. The dependence of the color indicators of chips on the total content of water-soluble antioxidants, in particular the flavonoid group, was established, namely, the higher the antioxidant value, the greater the concentration of flavonoids in the chips and, accordingly, the higher the concentration of red, yellow and blue pigments. On the basis of a comprehensive quality assessment, a sample of chips with a rational combination of recipe ingredients was selected: 70% of apple pomace puree, 30% of pumpkin puree, 1% of calendula powder, 10% of corn flour, providing an antioxidant content of 226.61 mg/100 g, bright and rich almond color.